Key variables for successful relationship marketing in business-to-business market. Case study: Telekom Malaysia Berhad (TM), Kota Bharu Kelantan / Norazian Mat Rifen - Mat Rifen, Norazian (2011)
This research is to study about customer satisfaction, commitment, and trust on the successful of relationship marketing in business-to-business market. The study was conducted in one of the telecommunication company which is, Telekom Malaysia Berhad, specifically in Telekom Malaysia Berhad (TM) Kota Bharu. This research is to identify the solutions that face by TM Kota Bharu. The main problem face is too difficult to maintain their customers and to achieve their sales target over the year. In addition, the lack of trust, commitment and also the customer satisfaction of the customers toward the company will be the main cause of the problems will affect their business performance. Due to the problems, there are certain circumstances why the research objective was developed. First, is to study whether customer satisfaction has associate to successful relationship marketing. Next is to determine whether commitment will lead to the successful of relationship marketing and the last objective is to study whether trust will influence in successful relationship marketing in business-to-business market. The findings of the research state that all the variables, customer satisfaction, commitment, and trust have a strong relationship with relationship marketing and lead to the successful of relationship marketing. Overall, based on the findings, there are several recommendations that have been suggested in order to help or to improve the relationship marketing between TM Kota Bharu and the whole TM with the customers. The organization should improve the service quality and product, in order to obtain customer satisfaction, build trust and improve commitment level